Notes on the augochlorine bee genus chlerogas (hymenoptera: halictidae) (2009)
Supplemental information to the earlier monograph of the rare bee genus ChlerogasVachal (Halictinae: Augochlorini) is provided. The recently identifi ed males of C.boliviensis Brooks and amp; Engel and C. cyaneus Brooks and amp; Engel are described andfi gured, including the fi rst account of the eversible endophallic structure for thegenus. In addition, C. cyaneus, previously known only from northern Ecuador, isnewly recorded from north-central Colombia.